Socio-Political Aspects of Russian Muslim Pilgrimage to Mecca in the XIX-Th Century - Gafarov, Anvar Ajratovich; Galeeva, Mariam Arslanovna (Cuestiones Políticas, 2020)
Starting from the middle of the 16-th century, during the foreign policy expansion increase, the ethno-confessional diversity of the Russian state was steadily increasing. The imperial policy aimed at assimilating non-Russian peoples sharply raised the issue of their identity preservation. For domestic Muslims, an important factor in cultural and confessional identity provision was the preservation and development of their traditional ties with the Islamic world. Various political, economic, cultural, and other contacts maintained with the countries of the Muslim East have become the basis for the stability of the Muslim community in Russia under imperial pressure. In this system, a special role was originally played by the Hajj (Muslim pilgrimage to the holy places in the Hejaz), which the official administration had to reckon with. The aim of the proposed study is to identify socio-political aspects, socio-political conditions, and the specifics of the Hajj implementation in the 19th century. After the analysis of office documentation, travel notes of Muslim pilgrims, and expert assessments of orientalists, the authors concluded that, despite the increasing opposition from the authorities, the significance of the Hajj intensifies in the 19th century. Hajj became not only the factor of opposition to imperial acculturation, but also a channel for presentation the ideas of renewal.